Estudio de las aplicaciones Web Empresariales, desarrolladas en el lenguaje de Programación Java, en los Frameworks Hibernate y Spring - Viejo Cavero, Diego Armando (2021)
This study seeks to establish the way in which large business web applications have been developed implementing the microservices architecture using the Hibernate and Spring frameworks in the Java programming language as the main tool, in the same way the differences that exist between the architecture of microservices and monolithic architecture. A bibliographic research is implemented where different sources are cited to determine the way in which these tools are integrated to give rise to new business web applications that have the capacity to satisfy the needs of millions of users around the world in real time, the way in which today's web applications still see the Java programming language as a solution despite the time it has regardless of the competition it has to deal with. The way in which microservices are developed using the Java programming language is analyzed, as well as the way in which the new features of the Spring framework are exploited in combination with the Hibernate Framework through object-relational mapping. A survey was carried out to focused groups of the programmer community to be able to establish to a certain extent the impact that the use of tools such as frameworks have when developing business web applications, likewise it seeks to establish the appreciation that developers have of using the Java programming language as a language that runs on the server, and the use that is given to it when developing microservices for large web applications.